Anti-plasmodial activity of artemether-lumefantrine-tinidazole on plasmodium falciparum infected humans - Oni, Akindele E.; Georgewill, Udeme O. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: The emergence of multi-drug resistant strains of Plasmodium falciparum has intensified the search for effective compounds. This study aimed to evaluates the combined effects of tinidazole and artemether/lumefantrine on human participants infected with P. falciparum. Methods: The study involved 25 non-infected adults as controls and 75 infected adults, divided into three groups of 25. The groups were treated orally with 1g of Tinidazole (T) twice daily for 3 days, an 8-hourly initial dose followed by 12-hourly 80mg/480mg doses of Artemether/Lumefantrine (AL) for 3 days, and a combination of 1g tinidazole and artemether/lumefantrine (80mg/480mg) for 3 days. Venous blood samples were taken on days 0, 4, and 14 to evaluate renal function, parasitemia, hematological parameters, lipid profiles, and antioxidant measures (catalase, SOD, glutathione peroxidase, and malondialdehyde). Results: The percentage recovery with AL, T, and the combination of T and AL was 88%, 92%, and 100%, respectively. Malaria patients exhibited significantly lower levels of red blood cells, hemoglobin, packed cell volume, low-density lipoprotein, high-density lipoprotein, total cholesterol, catalase, superoxide dismutase, and glutathione peroxidase, and higher levels of white blood cells, triglycerides, and malondialdehyde compared to the control group. Post-treatment, there was a modest reversal on day 4 and a significant return to normal ranges by day 14. Malaria infection did not affect urea or creatinine levels. Conclusions: Tinidazole shows potential as a treatment for P. falciparum, with enhanced efficacy when combined with artemether/lumefantrine.